Pieter Saenredam in Den Bosch - Hond, Jan de; Saenredam, Pieter Jansz. 1597-1665; Huys Janssen, Paul; Noordbrabants Museum (Eindhoven : Lecturis, 2013)
The Haarlem artist Pieter Saenredam (1597-1665) is best known for his cityscapes and drawings and paintings of church interiors. In the summer of 1632 Saenredam spent a month in Den Bosch. He stayed there with his cousin, the preacher Johannes Junius. Saenredam made in a short time in Den Bosch a varied number of drawings, including cityscapes, church interiors and monuments. Every drawing was precisely dated by him, giving us an accurate picture of its work in the summer of 1632. The works that resulted from Saenredams visit to Den Bosch are now, for the first time, brought together in a book published on the occasion of the exhibition in the renovated Noordbrabants Museum. It is about fourteen drawings and two paintings. Saenredam in Den Bosch contains many new facts and useful information about the works of one of the most outstanding painters of the Golden Age. 0Exhibition: Noordbrabants Museum, Den Bosch, the Netherlands (25.5.-21.7.2013).
Includes bibliographical references (pages 122-125).
Keywords: Saenredam, Pieter Jansz. -- 1597-1665; Saenredam, Pieter Jansz. -- 1597-1665; Travel -- 17th century -- Exhibitions; Travel; 's-Hertogenbosch (Netherlands); 17th Century (1601-1700); Travel